Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Discover comprehensive solutions to your questions from a wide network of experts on our user-friendly platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To find the inverse of the function [tex]\( f(x) = 2 - 2x \)[/tex], let's go through the process step by step.
1. Replace [tex]\( f(x) \)[/tex] with [tex]\( y \)[/tex]:
[tex]\[ y = 2 - 2x \][/tex]
2. Swap [tex]\( x \)[/tex] and [tex]\( y \)[/tex] to find the inverse function:
[tex]\[ x = 2 - 2y \][/tex]
3. Solve the equation above for [tex]\( y \)[/tex]:
[tex]\[ x = 2 - 2y \][/tex]
[tex]\[ x - 2 = -2y \][/tex]
[tex]\[ y = \frac{2 - x}{2} \][/tex]
4. Simplify the expression:
[tex]\[ y = 1 - \frac{x}{2} \][/tex]
Thus, the inverse function [tex]\( f^{-1}(x) \)[/tex] is:
[tex]\[ f^{-1}(x) = 1 - \frac{x}{2} \][/tex]
Now, let's compare this result with the given options:
- [tex]\( f^{-1}(x) = -\frac{1}{4}x + \frac{4}{5} \)[/tex]
- [tex]\( f^{-1}(x) = -\frac{1}{2}x + 1 \)[/tex]
- [tex]\( f^{-1}(x) = \frac{1}{2}x - 1 \)[/tex]
- [tex]\( f^{-1}(x) = \frac{4}{5} \)[/tex]
The correct function that matches our result [tex]\( f^{-1}(x) = 1 - \frac{x}{2} \)[/tex] is:
[tex]\[ f^{-1}(x) = -\frac{1}{2} x + 1 \][/tex]
Therefore, the correct answer is:
[tex]\[ f^{-1}(x) = -\frac{1}{2} x + 1 \][/tex]
1. Replace [tex]\( f(x) \)[/tex] with [tex]\( y \)[/tex]:
[tex]\[ y = 2 - 2x \][/tex]
2. Swap [tex]\( x \)[/tex] and [tex]\( y \)[/tex] to find the inverse function:
[tex]\[ x = 2 - 2y \][/tex]
3. Solve the equation above for [tex]\( y \)[/tex]:
[tex]\[ x = 2 - 2y \][/tex]
[tex]\[ x - 2 = -2y \][/tex]
[tex]\[ y = \frac{2 - x}{2} \][/tex]
4. Simplify the expression:
[tex]\[ y = 1 - \frac{x}{2} \][/tex]
Thus, the inverse function [tex]\( f^{-1}(x) \)[/tex] is:
[tex]\[ f^{-1}(x) = 1 - \frac{x}{2} \][/tex]
Now, let's compare this result with the given options:
- [tex]\( f^{-1}(x) = -\frac{1}{4}x + \frac{4}{5} \)[/tex]
- [tex]\( f^{-1}(x) = -\frac{1}{2}x + 1 \)[/tex]
- [tex]\( f^{-1}(x) = \frac{1}{2}x - 1 \)[/tex]
- [tex]\( f^{-1}(x) = \frac{4}{5} \)[/tex]
The correct function that matches our result [tex]\( f^{-1}(x) = 1 - \frac{x}{2} \)[/tex] is:
[tex]\[ f^{-1}(x) = -\frac{1}{2} x + 1 \][/tex]
Therefore, the correct answer is:
[tex]\[ f^{-1}(x) = -\frac{1}{2} x + 1 \][/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.